2021
DOI: 10.1107/s1600576721009365
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction investigation of copper tellurite glasses with high real-space resolution

Abstract: High real-space resolution neutron diffraction measurements up to 34 Å−1 were performed on a series of xCuO–(100 − x)TeO2 (x = 30, 40 and 50 mol%) glasses that were synthesized by the melt-quenching technique. The Fourier transformation of neutron diffraction structure factors was used to generate the pair distribution functions, with the first peak at 1.90 Å due to the overlapping Te–O and Cu–O atomic pairs. Reverse Monte Carlo (RMC) simulations were performed on the structure factors and the six partial atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In several binary and multicomponent glass systems the nearest neighbour correlation information cannot be extracted from the diffraction data due to the overlapping peaks of atomic pair correlation distributions (Kaur et al, 2020a). In such a scenario the reverse Monte Carlo (RMC) simulations are found to be more useful to calculate the partial atomic pair correlation distributions, which give accurate values of coordination number environments, bond lengths and bond angle distributions even at low-Q (momentum transfer function) values (Kaur et al, 2020a(Kaur et al, , 2019(Kaur et al, , 2021aMcGreevy & Pusztai, 1988;Fa ´bia ´n & Araczki, 2016). Alderman et al (2019) confirmed the existence of a wide range of Te-O bond lengths in the glassy TeO 2 network by synchrotron X-ray diffraction studies and this large variation in the shortrange structural properties is classified as short-range disorder and is a characteristic feature of tellurite glasses and not observed in other oxide glasses such as borate and silicate glasses.…”
Section: Introductionmentioning
confidence: 99%
“…In several binary and multicomponent glass systems the nearest neighbour correlation information cannot be extracted from the diffraction data due to the overlapping peaks of atomic pair correlation distributions (Kaur et al, 2020a). In such a scenario the reverse Monte Carlo (RMC) simulations are found to be more useful to calculate the partial atomic pair correlation distributions, which give accurate values of coordination number environments, bond lengths and bond angle distributions even at low-Q (momentum transfer function) values (Kaur et al, 2020a(Kaur et al, , 2019(Kaur et al, , 2021aMcGreevy & Pusztai, 1988;Fa ´bia ´n & Araczki, 2016). Alderman et al (2019) confirmed the existence of a wide range of Te-O bond lengths in the glassy TeO 2 network by synchrotron X-ray diffraction studies and this large variation in the shortrange structural properties is classified as short-range disorder and is a characteristic feature of tellurite glasses and not observed in other oxide glasses such as borate and silicate glasses.…”
Section: Introductionmentioning
confidence: 99%